Tryptophan reduces the degree of brown adipose tissue whitening in rats with visceral obesity - Yanko, Roman; Levashov, Mikhail; Safonov, Sergey (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The relationship between brown adipose tissue (BAT) and visceral obesity (VO) is a topic of growing interest in scientific and medical research. The aim of this work was to investigate the effect of L-tryptophan on histomorpho logical abnormalities in BAT induced by a high calorie diet (HCD). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The study was performed on male Wistar rats 3 months of age. Control rats (group I) were fed a stan dard diet. VO in animals (groups II and III) was modelled by exposure to an HCD (45% fat and 31% carbohydrates) for 12 weeks. The rats in group III were also given L-tryptophan (80 mg/kg). Histological preparations were prepared from the interscapular bodies of the BAT. Indicators of lipid metabolism, oxygen consumption, subcutaneous oxygen tension and basal temperature were measured in the rats. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. It was found that the group of rats on HCD lead to the development of VO, and histomorphological changes occur in BAT indicating a decrease in its activity. Supplementation with L-tryptophan reduced the structural abnormalities in BAT, name ly the accumulation of fat, the whitening of brown adipocytes, and prevented excessive loss of activity due to the deleterious effects of HCD. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Supplementation with L-tryptophan may have a potential benefit in preventing the development of excessive VO by preserving BAT activity.